Implementation of Green Accounting and Sustainability Performance Critical Reflections, Challenges and Opportunities - Haliding, Safri; Haerunnisa, Rosyada; Arsyad, Kamaruddin; Sakti, Muhammad Rizky Prima; Nanda, Sahabuddin (Universitas Islam Negeri Alauddin Makassar, 2024)
The growing awareness of environmental issues and the pressing need for sustainable development have led to significant changes in the corporate world. Traditional accounting practices are increasingly seen as insufficient for addressing the broader impacts of business activities on the environment and society. This study analyses the implementation of green accounting and sustainability performance in the business and decision-making of corporate activities and promote sustainability. The study also highlights the critical reflections of green accounting. The study find that the development of green accounting reflects a growing recognition of the need to incorporate environmental considerations into business operations and decision-making that it will be crucial for organizations to adopt best practices and address the barriers to successful implementation and its impact on sustainability performance that the critical aspects of green accounting is its ability to improve a company's sustainability performance such as government policies and regulations, plays a crucial role in ensuring the successful implementation of green accounting and its impact on environmental preservation.